Projeto – bancada experimental didática de flambagem - Vitorino, Ilkenne Cassio Rodrigues (Universidade Federal Rural do Semi-Árido, 2018)
The purpose of the current study was the building of an educational experimental row of seats, to improve methodology of learning and teaching engineering mechanics II. This study was supported on concept of Euler`s column buckling included in syllabus. This work was motivated by the students’ difficulty to visualize the physical phenomenon in practice, in this way, a use of experimental didactics that reproduces the contents learned in the classroom is very important. The design and execution of this row of seats will facilitate the visualization and understanding of the students regarding the phenomenon of buckling of columns, according to Euler, submitted to different support configurations. Supporting the professor as it is a practical form and can be used in the classroom and in the laboratory. Seeing the importance of practice in the study of technological sciences as well as in engineering, this study also addressed the conceptual theory of work in a simplified, for easy understanding. Finally, since UFERSA does not have laboratories for some programs, such as engineering mechanics II, and investments for education in Brazil are increasingly scarce, a construction of an experimental didactic row of seats of low cost is a differential point in the teaching-learning aspect of this curricular component as important as engineering.
Monografia
Keywords: Construção de bancada experimental didática; Flambagem de colunas; Flambagem de Euler; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA